Effective SrWO4/TiO2 Heterojunction with Enhanced Carriers Separation and Transfer for Photocatalytic Methane Oxidation. Issue 24 (17th March 2023) - Huang, Min; Zhang, Shuyi; Gan, Yongping; Liu, Jin; He, Zhanjun; Lin, Tiejun; Yu, Fei; Dai, Yuanyuan; Niu, Qiang; Zhong, Liangshu
Abstract: Photocatalytic methane oxidation to oxygenates with promising performance remains as a grand challenge due to the low productivity and severe overoxidation. Herein, SrWO4 /TiO2 heterojunction was developed for photocatalytic methane oxidation with O2 to liquid oxygenates ( Please replace "oxygenates" with "oxygenated")products under mild reaction conditions. The optimized SrWO4 /TiO2 catalyst exhibited high productivity of 13365 μmol/g with high selectivity of 98.7 % for oxygenates. Benefited from the intimate heterojunction interface of SrWO4 /TiO2, the constructed I‐type heterostructure improved the separation and transfer of photogenerated carriers, and a high‐speed transfer channel for photogenerated carriers was fabricated. Simultaneously, the special band structure can increase the amount of photogenerated electrons and holes on the TiO2 surface, which promoted the formation of reactive oxygen species to enhance liquid oxygenates productivity. Abstract : Highly effective SrWO4 /TiO2 heterojunction photocatalysts were fabricated for photocatalytic methane oxidation into oxygenates with O2 under mild conditions. The high‐speed transfer channel between SrWO4 and TiO2 on SrWO4 /TiO2 photocatalysts promoted separation and transfer of photogenerated carriers, which enhanced the generation of oxygenates with high selectivity.